Understanding brief illness perception among cardiac patients: a preliminary study - Sukhbeer Kaur Darsin Singh; Khatijah Lim Abdullah; Imran Zainal Abidin; Abqariyah Yahya; Anwar Suhaimi (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Illness perceptions involve personal beliefs that patients have about their illness and may influence health behaviour considerably. This preliminary study evaluates the understanding of illness perception among cardiac patients’ and correlations of each of the items. Methods: A preliminary study was conducted using the on Brief Illness Perception Questionnaire (BIPQ) in a tertiary hospital among 40 cardiac patients. Ethical approval was obtained from the institution ethical committee. There are 9 items in the BIPQ with 0-10 response scale measuring causal factors and an open-ended item. Items 1 to 5 assesses on the cognitive illness perception which comprises of consequences, timeline, personal control, treatment control and identity. Item 6 and 8 are on emotional response and item 7 is on coherence. Results: The overall mean score of the 8 items of BIPQ was 7.04 (1.07) with the highest mean for item 4 on treatment control and item 6 on personal control at 8.02 (0.92) and 7.03 (1.77) respectively while the lowest mean was item 7 on understanding at 6.63 (1.83). The causal factor for the open-ended question was mostly on consumption of fatty food intake, sedentary lifestyle and stress at work. Perceiving personal control was significantly being affected by perceiving treatment control for the cardiac disease (r=0.50) and being concerned about their cardiac symptoms was significantly related to perceiving consequences of the disease (r =0.54), perceiv¬ing identity (r=0.75) and perceiving emotional control (r=0.67). Perceiving emotional control on their symptoms was significantly related to perceived consequences on cardiac disease (r=0.51), perceived identity (r=0.53) and perceived concern on cardiac disease (r=0.67). Conclusion: The results shown significant correlations with relevant outcomes measures. It is useful in clinical practice to assess and potentially modify patient’s perceptions on under¬standing, emotional control, personal control, consequences and perceived concerned over their cardiac disease.